2015
DOI: 10.5125/jkaoms.2015.41.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Aplastic anemia and dental implant rehabilitation: a clinical trial

Abstract: The purpose of this study was to investigate implant-supported restoration as a technique for restoring missing teeth in patients with aplastic anemia. Recurrent bleeding from wound sites leads to persistent release of iron in the tissue. Excessive iron in tissue is related to clinical findings, including fibrosis, poor wound healing, and high level of angiogenesis, which are possible etiological factors of reduced osseointegration. A 44-year-old female patient with aplastic anemia was treated with multiple en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a study on wound complications in laryngectomized patients, prior radiation therapy, diabetes mellitus, preoperative hypoalbuminemia, anemia, and thrombocytosis were found to be independent etiological factors for wound complications [11]. In patients with aplastic anemia, it has been shown that anemia can be kept under control without disrupting wound healing during dental implant application [12]. Cleft palate can be associated with Diamond-Blackfan anemia [13,14].…”
Section: Anemiamentioning
confidence: 99%
“…In a study on wound complications in laryngectomized patients, prior radiation therapy, diabetes mellitus, preoperative hypoalbuminemia, anemia, and thrombocytosis were found to be independent etiological factors for wound complications [11]. In patients with aplastic anemia, it has been shown that anemia can be kept under control without disrupting wound healing during dental implant application [12]. Cleft palate can be associated with Diamond-Blackfan anemia [13,14].…”
Section: Anemiamentioning
confidence: 99%